Respuesta :

Answer:

-1/2 and -1

Step-by-step explanation:

Our system of equations is:

y = 2x²

y = -3x - 1

We can set the y's equal to each other:

y = 2x² = -3x - 1

Now, we have:

2x² = -3x - 1

Move all the terms to one side by adding both sides by 3x and 1:

2x² + 3x + 1 = 0

We must factor this quadratic. Note that the factoring is:

(2x + 1)(x + 1) = 0

Our solutions are now:

2x + 1 = 0           OR           x + 1 = 0

x = -1/2                                x = -1

.

Thus, our solutions are -1/2 and -1.

ACCESS MORE